Pembuatan Aplikasi âPetra Then and Nowâ tentang Semua Kegiatan di Universitas Kristen Petra - Linggadihardja, Dian Christiani; Handojo, Andreas; Wibowo, Adi (Jurnal Infra, 2015)
In this well developed era, technology becomes a part that can not be neglected. Speed in searching for information has become crucial and the old ways are gradually left behind. It is not surprising that the internet takes an important role in life; website has become a common media to look for information.This thesis is meant to ease the users who look for information about events in Petra Christian University. By using web, users can see list of events, not only events that are happening or upcoming (displayed as a calendar), but also past and historical events (displayed as a timeline) in Petra Christian University.Besides being facilitated in looking for event information, users also can see documentation of historical events and be reminded of important things that had already happened.